Efforts to Improve Social Studies Learning Achievement of Grade VIII.1 Students at SMPN 33 Padang through the Teaching the Right Level (TARL) Approach - Haidir Haidir; Aisiah Aisiah; Nice P Numarmita (UIN Fatmawati Sukarno Bengkulu, 2025)
This classroom action research aims to improve the learning outcomes of Social Science (IPS) students in class VIII.1 at SMPN 33 Padang. The main issue was the low average score of 63.33, with only 50% of students achieving the minimum passing grade (≥70). To address this issue, the study utilized the Teaching at the Right Level (TaRL) approach integrated with a problem-based learning model. The research employed a classroom action research method conducted over two cycles. Data collection techniques included learning outcome tests, observations, and interviews, while data analysis was performed using descriptive qualitative and quantitative methods. The results demonstrated significant improvements. In the first cycle, the average score increased to 69.89, with 65% of students achieving the minimum passing grade. However, observations revealed that some students remained passive during learning. Based on these reflections, the second cycle focused on enhancing student activity and engagement, resulting in an average score of 83.3, with 90% of students meeting the passing criteria. Furthermore, students showed greater enthusiasm and active participation in group discussions. In conclusion, the TaRL approach implemented through the problem-based learning model effectively enhanced the learning outcomes of Social Science students. This study recommends that teachers adopt similar approaches and educational institutions support their implementation.